Female teachers of children with special needs bouyancy, compassion fatigue, and locus of control. - Velete, Eugene; Yranela, Ana Maria Barbara (Miag-ao, Iloilo University of the Philippines Visayas, College of Arts and Sciences, Division of Social Sciences, 2009)
The study was conducted to determine the factors that contribute to the buoyancy of female teachers of children with special needs, as well as their potential for compassion fatigue. Also, the study tried to identify the locus of control of the teachers in dealing with setbacks and rewards of their profession. Twelve (12) teachers from three different Special Education schools in Iloilo City, who have been working for at least two years a s teachers of children with special needs were the respondents for the study., The instruments used were the Compassion Satisfaction/Fatigue Self-Test for Helpers adapted from C.R Figley by B. Hudnall Stamm and and the Rotter's Locus of Control Scale. An interview guide was also developed to identify the factors that contribute to the teacher's buoyancy. It was identified that physical stress is the main stressor of the female teachers, and that the factor significantly contributes to their buoyancy or the way they handle everyday stress in their profession, like aformentioned, is their love for children. Furthermore, the scales revealed that 9 (75 percent) of the teachers were at high potential for compassion fatigue. With regards to locus control, 8 (66 percent) were internally controlled and 4 (33 percent) were externally controlled.
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Teachers of children with special needs